Understanding the extent of stakeholder reporting and materiality disclosures in integrated reports, sustainability reports and websites of companies listed on JSE - Joffe, Philippa Erin (My University, 2018)
This research examined the extent of stakeholder reporting disclosures and materiality disclosures in the integrated reports, sustainability reports and websites of JSE listed companies. This study investigated how companies disclose their materiality determination process and if they disclose their stakeholder engagement activities. A disclosure checklist, based on the relevant academic and professional literature, was developed by the researcher to quantify and investigate the current reporting disclosures relating to materiality and stakeholder engagement in 2016. The results highlighted the relationship between the disclosures made by companies to determine materiality and stakeholder engagement disclosures in the related reports. In this study, materiality is a key reporting principle in preparing the integrated report and sustainability report. The results of this research, supported by prior literature, have identified that stakeholder engagement and materiality are related concepts. The King Report on Corporate Governance emphasizes that stakeholder inclusivity is a key reporting principle as stakeholder identification and engagement facilitates the identification and understanding of the material concerns, issues, perceptions, needs and expectations of stakeholders.
Keywords: Corporation reports--South Africa; Corporate governance--South Africa